Mental health patterns of physiotherapists in South Africa during COVID-19 - Nabeelah Bemath; Nicky Israel; Tasneem Hassem (AOSIS, 2023)
Background: While attention has been drawn to the impact of the coronavirus disease 2019 (COVID-19) pandemic on the mental health of healthcare workers generally, little is known regarding mental health changes over time in frontline and non-frontline physiotherapists during this period. Objectives: Our study aimed to investigate differences in mental health trends among frontline and non-frontline physiotherapists across three time periods during the pandemic. Method: Survey-based data were collected from 366 practising physiotherapists across three time periods during the pandemic (Time 1: n = 171; Time 2: n = 101; Time 3: n = 94). Variations in reported mental health of frontline and non-frontline respondents generally and over time were analysed using comparative statistical techniques and trend analysis. Results: Frontline physiotherapists reported significantly lower levels of general mental well-being and resilience, and significantly higher levels of burnout and maladaptive strategy use. Only frontline physiotherapists' general mental well-being and resilience decreased over time, whereas depression decreased over time for both groups. Anxiety decreased over time for non-frontline physiotherapists but initially decreased and then increased for frontline physiotherapists. Burnout increased initially and then decreased for non-frontline physiotherapists. Conclusion: Varying mental health trends were found between frontline and non-frontline physiotherapists over time. Nuanced mental health interventions that consider the period of the pandemic and degree of exposure are needed. Clinical implications: Understandings of the mental health trajectories experienced by physiotherapists across the pandemic can inform long-term, targeted interventions that effectively enhance well-being, retention, and sustainability of practitioners, and thus the care delivered, in the healthcare system.